PENDAMPINGAN PEMBINAAN KARAKTER MELALUI PEMBELAJARAN BIOLOGI: STRATEGI EFEKTIF MENUMBUHKAN SIKAP MORAL SISWA - Eka Kartikawati; Mayarni, Mayarni; Dharma, Agus Pambudi (LPPM Universitas Islam 45 Bekasi, 2025)
Community service activities that focus on Character Development Assistance through Biology Learning have been successfully implemented. This program aims to foster students' moral attitudes by integrating moral values into Biology learning and encouraging students to understand and apply values such as caring for the environment, cooperation, and honesty in the learning process. The method of implementing activities in this training is the Participatory Action Research (PAR) Method as a form of counseling that involves the active participation of service participants. PAR methods can be used to empower participants in the process of change. The results of the activity showed an increase in understanding among both teachers and students about the importance of teaching moral values. In addition, this activity also makes a positive contribution to the formation of students' character. Nonetheless, the authors suggest the need for further evaluation to assess the long-term impact of these activities, as well as the development of more comprehensive and sustainable learning models. It is also recommended that the dissemination of the results of activities to other schools can be felt more widely. This activity is a form of accountability for the implementation of community service programs.